Designing Futures for an Age of Differentialism - Ely, Philip (Taylor & Francis, 2020)
Humanity appears to be confronting an increasing number of health, economic, political, environmental, and social crises, which have been mainly brought about by human action itself. Whilst design has been complicit in such action, the paradigmatic strength of Design Thinking has amplified the agency of designers, who now have the opportunity to reorient toward a way of designing which harnesses cultural difference to confront these crises. Drawing on Lefebvre’s ideas of “difference,” Escobar’s “autonomous design,” and through a process of cultural reflexivity, I propose an approach to design – differential design – as a practical endeavor which sensitively and respectfully draws upon different cultural perspectives and traditions to design for the future. I share empirical examples of three methods: “worldviews,” “generative scribing,” and the application of “rhetoric.” Modestly and pragmatically, these may be used to shift the ontological perspectives of designers in the social and political project of designing equitable and empathic futures.